The vasorelaxant effect of Hibiscus sabdariffa linn. Polyphenol-rich extract (HPE) on rat’s isolated aorta - Ahmad Rohi Ghazali; Asmariah Ahmad; Lim, Yi Cheng; Shafreena Shaukat Ali; Satirah Zainalabidin (Penerbit Universiti Kebangsaan Malaysia, 2018)
Hibiscus sabdariffa Linn. or also known as roselle which is rich in polyphenols, has been demonstrated to cause lowering of blood pressure in animal and clinical settings. However its exact mechanism of action particularly from polyphenolic compounds is not clearly understood. Therefore, we aimed to determine the effects of H. sabdariffa polyphenol extract (HPE) towards vascular reactivity and its mechanism of action. The HPE was studied on isolated thoracic aortic rings from normal Sprague-Dawley rats, suspended in a 15-ml organ chambers containing Krebs-Henseleit solution. The changes in tension were recorded by isometric transducer connected to data acquisition. HPE relaxed the contraction induced by phenylephrine (PE, 1 μM) in similar pattern for both endothelium-intact and endothelium denuded aortic rings in dose-dependent manner 0.1 ~ 0.9 mg/ml. The pretreatment with atropine (1 μM), a competitive muscarinic antagonist, and propranolol (1 μM), a non-selective beta- blocker did not alter HPE vasorelaxation response. In addition, HPE did not inhibit the contraction induced by extracellular Ca2+ precontracted by PE (1 μM) or KCl (60 mM), in Ca2+ -free solution, suggesting that the relaxation effect of HPE was not via inhibition of calcium channels. In conclusion, HPE demonstrated vasorelaxation effects on rat thoracic aorta although the underlying mechanism is still unknown. The vasorelaxation effect could be via angiotensin type 1 receptor inhibition in the vascular smooth muscle cells or the activation of hyperpolarizing K+ channel.